A typology of responsibility for coastal flood risk adaptation - van der Plank, Sien; Brown, Sally; Tompkins, Emma L.; Nicholls, Robert J. (Frontiers in Marine Science, 2022)
The management of coastal flood risk is adapting to meet the challenges and increased risks posed by population change as well as by climate change, especially sea level rise. Protection is being targeted to areas where the benefits are highest, while elsewhere there is a shift towards more localized “living with floods” and “resilience” approaches. Such decentralized approaches to flood risk management (FRM) require a diverse range of stakeholder groups to be engaged as “flood risk citizens”. Engagement of households in FRM is central to this process. Despite significant research on stakeholder engagement in coastal and flood risk management, there is less focus on the nature of responsibility in coastal adaptation. There is no framework by which to assess the different types of responsibility in hazard management and adaptation, and little research on the implications of expecting these responsibilities of stakeholder groups. In this paper, we identify five types of responsibility that are embedded throughout the disaster risk reduction cycle of managing coastal flooding. We build this “typology of responsibility” on existing work on the evolution of stakeholder engagement and stakeholder responsibility relationships in risk management processes, and a dataset of institutional stakeholder interviews and households surveys conducted across three case studies in England, the United Kingdom, in 2018 and 2019. We analyze the interviews using thematic analysis to explore institutional stakeholder perceptions of responsibility in coastal FRM, and analyze the household survey through descriptive and inferential statistics. By developing the first disaster risk reduction focused typology of responsibility for coastal flooding, we provide researchers and decision-makers with a tool to guide their planning and allocation of responsibilities in risk management for floods and other climate-driven hazards.